PARAMAGNETIC AND FERROMAGNETIC ANISOTROPY OF MAGNETIC SUSCEPTIBILITY IN MIGMATITES: MEASUREMENTS IN HIGH AND LOW FIELDS AND KINEMATIC IMPLICATIONS - Ferre E.C.; Martin-Hernandez F.; Teyssier Ch.; Jackson M. (My University, 2004)
The separation of paramagnetic and ferromagnetic anisotropy of magnetic susceptibility (AMS) is achieved in this study by using a vibrating sample magnetometer and a torque magnetometer performing directional anisotropy measurements in sufficiently high fields to saturate the ferromagnetic phases. The studied material, a migmatite from Minnesota, has a magnetic mineralogy characterized by ferrimagnetic multidomain titanomagnetite, paramagnetic biotite and a diamagnetic quartzo-feldspathic matrix. The low-field AMS represents the sum of ferromagnetic and paramagnetic contributions because the quartz contribution can be neglected, its magnetic susceptibility being two orders of magnitude smaller than that of biotite. In contrast, measurements in a high field isolate the paramagnetic component of the magnetic fabric. The high-field AMS is consistent between specimens and correlates well with measurements done using the torque magnetometer. The magnetic fabrics of the ferromagnetic and of the paramagnetic minerals are not co-axial, i.e. the subfabrics of the biotite and the magnetite are distinct. We propose that this non-coaxiality is due to a vorticity component during regional deformation and that it reflects the general conditions of deep crustal orogenic deformation.
Keywords: AMS; HIGH-FIELD; MAGNETIC ANISOTROPY; MIGMATITE; PARAMAGNETISM